Scope and Challenges of 3D Printing in Organ Transplantation - Shah, Naman; Jain, Sarthak; Jain, Priyal; Thakur, Mamta (Current Biochemical Engineering (Discontinued), 2021)
Background: The influx of 3D printing in organ transplantation is currently a rigorous area of research, and its success is still cynical. This review article focuses mainly on the scope and challenges in the applications of 3D printing in organ transplantation. The basic idea of the article is to highlight the current status of 3D printing in the area of organ transplants. Introduction: The review article covers the highlights about the 3D printing, major steps incurred in the 3D printing of organs, challenges in the 3D printing and transplantation of organs, and future prospects (scope) in the area with special reference to the problem and failures encountered in organ transplantation of 3D printed organs. Methods: The findings from available studies have been consolidated in the review article to provide insight into the scope and challenges in the area of 3D printed organ transplantation. Results: In the review study, it has been found that there are certain limitations of the 3D printed material based on the survival and multiplication in the in-vivo environment, which subsequently leads to the bio incompatibility of the organs. In addition to this, some other limitations which provide further scope of research in this area are also included. Conclusion: It has been concluded that 3D printing is an emerging solution in organ transplantation and prosthetics, but still more refinement and technological advancement is needed to make it a completely feasible solution. Doctors, scientists, and engineers need to work in a cross-disciplinary manner to overcome the limitations and develop this technique further for the betterment of mankind.
Keywords: prosthetics